Reemerging Jewish Culture in Germany : Life and Literature Since 1989. - Gilman, Sander L. (NYU Press, 1994)
How can there by a Jewish culture in today's Germany? Since the fall of the Wall, there has been a substantial increase in the visibility of Jews in German culture, not only an increase in the number of Jews living there, but, more importantly, an explosion of cultural activity. Jews are writing and making films about the central question of Jewish life after the Shoah. Given the xenophobia that has marked Germany since reunification, the appearance of a new Jewish is both surprising and normalizing. Even more striking than the reappearance of Jewish culture in England after the expulsion and.